STUDI KASUS KESULITAN BELAJAR MATEMATIKA PADA REMAJA - Dewi Handayani Harahap dan Richanatus Syarifah (LPPM Universitas Proklamasi 45, 2015)
Mathematical ability is crucial for students since it contributes to their cognitive development and also their graduation. Student with low math ability is likely to be a school dropout. However, the math ability is influenced by two factors, internal and external factors. The internal factorsare numerous such as math anxiety, negative perception toward math, unpleasant experience about math, and low selfefficacy on math. The external factors are also numerous i.e. negative perceptions among math teachers on student's ability, unprofessional teacher, uncreative teacher, and punitive teacher. Two subjects participated in this preliminary research. One subject has positive perception toward math, whilst the rest has negative perception. This research intends to understand the factors contributing to the low score on math. This study revealed that student with positive perception is more likely to enjoy math learning process and able to cope with boredom. Student with negative perception, on the other hand, has difficulties in learning process and tend to boredom. Several limitations of this preliminary research are discussed.